Heat-resistant aluminum-silicon alloy material and preparation method thereof
By adding La, Ce, Ho, Nd, Yb and Al3Zr to aluminum-silicon alloys, a fine grain structure is formed, which solves the problems of grain growth and hardness decay in aluminum-silicon alloys at high temperatures, achieves high-temperature stability of the material and simplifies the preparation process, making it suitable for light automotive parts.
Patent Information
- Application Number
- CN202511257345.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-04
- Publication Date
- 2025-10-28
AI Technical Summary
Existing aluminum-silicon alloy materials exhibit grain growth and severe hardness reduction in thermally exposed environments. Furthermore, their preparation process is complex, requires sophisticated equipment, and results in unstable material properties.
Adding La, Ce, Ho, Nd, and Yb to aluminum-silicon alloys forms rare earth phases and Al3Zr dispersion strengthening phases. Annealing and aging treatments form fine grain structures, inhibit grain growth, and purify the melt by combining rare earth elements with impurities.
It maintains good hardness and elongation at high temperatures, has stable material properties, is easy to operate, and is suitable for industrial production.
Smart Images

Figure CN120843904A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to an aluminum alloy, specifically to a heat-resistant aluminum-silicon alloy material and its preparation method. Background Technology
[0002] Aluminum-silicon alloys have long been considered promising materials for manufacturing lightweight vehicles due to their low density, excellent casting properties, and good mechanical properties, and are widely used in the automotive industry. These characteristics, coupled with good thermal conductivity, low thermal expansion, and enhanced wear resistance due to silicon, make them ideal for lightweight, high-performance components, such as engine parts exposed to harsh conditions and thermal cycling. Aluminum-silicon microalloying significantly improves the overall mechanical properties of the material by incorporating various reinforcing rare earth elements into the aluminum matrix, and the process is simple and does not require highly specialized technical skills.
[0003] Rare earth atoms have large atomic radii, making them prone to segregation at grain boundaries rather than uniform dispersion. Furthermore, the diffusion rate of rare earth elements in a metal matrix is 1-2 orders of magnitude lower than that of copper and zinc, making it difficult to achieve uniform distribution through heat treatment. This method uses the addition of composite rare earth elements to suppress grain growth under heat exposure at 200℃ and 300℃.
[0004] Chinese patent (CN 118773491A) discloses a heat-resistant aluminum-silicon alloy material and its preparation method. It employs mechanical and electromagnetic stirring to add Ni-coated red mud to an aluminum-silicon-copper-nickel-magnesium alloy. The Ni coating improves the wettability of the red mud with the substrate material. By adding red mud with different compositions of Ni to the alloy and then subjecting it to T6 heat treatment, the Vickers hardness and room-temperature tensile strength of the substrate material are significantly improved. However, this technology also has some drawbacks, namely the complexity of the operation. The complexity of the red mud composition can lead to many uncontrollable variations and defects in the resulting material. Furthermore, the red mud contains a relatively high amount of Fe, and excessive Fe can significantly reduce the material's hardness, elongation, and toughness.
[0005] Compared with the Chinese patent (CN 116005022A) on a high-performance cast aluminum-silicon alloy and its preparation method, the high iron content (0.15-0.3%) results in a low elongation rate. In addition, the preparation process requires complex ultrasonic treatment, so the overall process is complex and the equipment requirements are high. Summary of the Invention
[0006] The purpose of this invention is to provide a heat-resistant aluminum-silicon alloy material and its preparation method, which solves the problems mentioned in the background. By adding La, Ce, Ho, Nd and Yb to the aluminum-silicon alloy to form rare earth phases and Al3Zr dispersed strengthening phases to inhibit grain growth, the material still maintains good hardness in a heat-exposed environment.
[0007] To achieve the above objectives, this invention provides a heat-resistant aluminum-silicon alloy material, the chemical formula of which is: Alx1Six2(LaCe)x3Hox4Ndx5Ybx6Zr; the alloy composition comprises, by mass percentage, 2-3% Si, 2.5-3.5% LaCe (La to Ce mass percentage 13:7), 1-2.5% Ho, 1-2.5% Nd, 0.5-1% Yb, 0.3-0.5% Zr, with the remainder being Al, incidental elements, and unavoidable impurities.
[0008] The ingot is subjected to annealing and aging processes in sequence, followed by water cooling. The annealing process involves quenching at 400℃ for 2 hours and then at 530℃ for 5 hours, followed by aging at 160℃ for 12 hours.
[0009] In the above chemical formulas, x1 represents the mass of Si element, which accounts for 2-3% of the total mass of the heat-resistant aluminum-silicon alloy. x2 represents the sum of the masses of La and Ce elements, which accounts for 2.5-3.5% of the total mass of the heat-resistant aluminum-silicon alloy. x3 represents the mass of Ho element, which accounts for 1-2.5% of the total mass of the heat-resistant aluminum-silicon alloy. x4 represents the mass of Nd element, which accounts for 1-2.5% of the total mass of the heat-resistant aluminum-silicon alloy. x5 represents the mass of Yb element, which accounts for 0.5-1% of the total mass of the heat-resistant aluminum-silicon alloy. x6 represents the mass of Zr element, which accounts for 0.3-0.5% of the total mass of the heat-resistant aluminum-silicon alloy.
[0010] As one of the preferred embodiments, the present invention provides a heat-resistant aluminum-silicon alloy material, wherein x1 is 2, x2 is 2.5, x3 is 1, x4 is 1, x5 is 0.5, and x6 is 0.3.
[0011] As one of the preferred embodiments, the present invention provides a heat-resistant aluminum-silicon alloy material, wherein x1 is 3, x2 is 3.5, x3 is 2, x4 is 2.5, x5 is 1, and x6 is 0.5.
[0012] As one of the preferred embodiments, the present invention provides a heat-resistant aluminum-silicon alloy material, wherein x1 is 2.5, x2 is 3, x3 is 1.5, x4 is 1.5, x5 is 1, and x6 is 0.4.
[0013] As one of the preferred embodiments, the present invention provides a heat-resistant aluminum-silicon alloy material, wherein x1 is 2.4, x2 is 3, x3 is 2, x4 is 2, x5 is 0.7, and x6 is 0.4.
[0014] The present invention discloses a method for preparing a heat-resistant aluminum-silicon alloy material, comprising the following steps:
[0015] Step 1: Raw material mixing: According to the stated mass percentage, alloys of different compositions are mixed and added to the smelting furnace for smelting;
[0016] Step 2: Ingot preparation: After refining with refining agent at least twice, the ingot is cast and air-cooled;
[0017] Step 3: Heat treatment process: The raw material of the ingot is subjected to heat treatment to obtain heat-resistant aluminum-silicon alloy material.
[0018] Preferably, in step 1, the smelting temperature is 800-820℃, and in industrial applications, the heating rate of the smelting furnace can be 4-6℃ / min.
[0019] In this invention, the furnace used for smelting can be a pit-type electric resistance furnace. Of course, other smelting furnaces are also applicable to this invention.
[0020] In this invention, in step 2, after at least two refining processes, the molten liquid temperature is reduced to 720°C and then poured into a mold preheated to 200°C and coated with zinc oxide paint, and then cooled to room temperature.
[0021] In this invention, the refining agent used for refining includes hexachloroethane.
[0022] As a preferred embodiment, in step 3 of the present invention, the ingot annealing process is performed at 400℃ / 2h + 530℃ / 5h, followed by a two-stage aging treatment at 100℃ / 2h + 160℃ / 10h to obtain the heat-resistant aluminum-silicon alloy material.
[0023] The heat-resistant aluminum-silicon alloy material developed and prepared in this invention exhibits excellent heat resistance. After prolonged heat exposure at different temperatures, the decrease in hardness is significantly lower than that of existing products or products obtained using existing technologies. Specifically, after continuous heat exposure at 200℃ for 300 hours, the Brinell hardness decreases by less than or equal to 0.1% compared to products that have undergone two-stage aging. After continuous heat exposure at 300℃ for 300 hours, the Brinell hardness decreases by less than or equal to 10%, and can even be less than or equal to 9%, compared to products that have undergone two-stage aging.
[0024] The heat-resistant aluminum-silicon alloy of the present invention is easy to operate and has a high elongation (≥4.77%).
[0025] The rare earth elements (La, Ce, Ho, Nd, Yb) selected in this invention have high chemical reactivity and preferentially combine with impurities such as hydrogen, oxygen, and sulfur in the melt to form high-melting-point rare earth compounds, thereby purifying the aluminum melt. These compounds are mainly distributed at grain boundaries during solidification, reducing the formation of harmful low-melting-point phases (such as Fe-Si phase) at grain boundaries, improving the stability of grain boundaries at high temperatures, and inhibiting grain boundary weakening. The appropriate amounts and complementary combinations of rare earth elements (La, Ce, Ho, Nd, Yb) effectively refine the primary Si phase and eutectic Si phase, and refine α-Al dendrites. Smaller, more rounded Si phases and finer grain structures are inherently more stable at high temperatures and less prone to coarsening or softening. Furthermore, nanoscale Al3Zr phases are formed, and during heat treatment (homogenization or aging after solution treatment), fine, coherent, and ordered L12-structured Al3Zr nanoparticles precipitate, inhibiting recrystallization and grain growth at high temperatures and maintaining a fine-grained structure.
[0026] (1) The smelting and heat treatment process of the present invention is simple to operate and does not involve complicated processes, which facilitates its promotion and application in industry and has broad application potential in the field of microalloying of heat-resistant aluminum-silicon alloy materials.
[0027] (2) The heat-resistant aluminum-silicon alloy was annealed at 400℃ / 2h+530℃ / 5h and then subjected to a double-stage aging treatment at 100℃ / 2h+160℃ / 10h, resulting in a Brinell hardness of 72.3HB.
[0028] (3) After continuous heat exposure at 200℃ for 300h, the Brinell hardness is 72.1HB. After heat exposure at 300℃ for 300h, the Brinell hardness is 66.04HB. Before heat treatment, the tensile strength of the as-cast alloy is 169.6MPa and the yield stress is 93.7MPa. At 200℃, the tensile strength is 109.1MPa, and the elongation remains at 5.3%. After high-temperature treatment, the alloy still has good elongation.
[0029] (4) Aluminum alloy and appropriate and matched rare earth elements synergistically generate lamellar Al 11 The eutectic phase of (Ce,La)3 can significantly refine the primary α-Al matrix, Al 11 (Ce,La)3 has an extremely low diffusion coefficient, making it difficult to dissolve or coarsen at high temperatures. Al3Nd has a cubic L12 structure and is not easily coarsened at high temperatures. Si undergoes a eutectic reaction L→α-Al+Si within the aluminum alloy, resulting in a lamellar structure of eutectic silicon. Al3Zr significantly improves the overall performance of aluminum alloys through multiple mechanisms, including grain refinement, enhanced high-temperature stability, strengthened mechanical properties, and optimized corrosion resistance. Attached Figure Description
[0030] Figure 1The image shows the XRD pattern of the heat-resistant aluminum-silicon alloy material obtained in Example 1.
[0031] Figure 2 SEM image of the as-cast heat-resistant aluminum-silicon alloy material obtained in Example 1;
[0032] Figure 3 Here is a SEM image of the annealed heat-resistant aluminum-silicon alloy material obtained in Example 1;
[0033] Figure 4 The image shows the tensile curves of the as-cast heat-resistant aluminum-silicon alloy material obtained in Example 1 at room temperature and 200 degrees Celsius. Detailed Implementation
[0034] The present invention will be further described below with reference to specific accompanying drawings and embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Any changes, substitutions, or replacements made without departing from the spirit and principle of the invention are included within the scope of protection of the invention. Furthermore, it should be understood that after reading the contents of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims and are all within the scope of protection of the invention.
[0035] Unless otherwise specified, all reagents, instruments, and equipment used in this invention are those commonly used by those skilled in the art. The raw materials used in this invention are all industrial pure aluminum, as well as Al-20Si, Al-20(LaCe), Al-10Ho, Al-10Nd, Al-10Yb, and Al-5Zr alloys.
[0036] Example 1
[0037] S1: According to the designed chemical formula: Al-2.4Si-3(LaCe)-2Ho-2Nd-0.7Yb-0.4Zr, 900g Al, 600g Al-20Si, 750g Al-20(LaCe), 1000g Al-10Ho, 1000g Al-10Nd, 350g Al-10Yb, and 400g Al-5Zr are sequentially added to a pit-type resistance furnace at 800℃ for melting. During this process, slag on the melt is removed before each addition of the intermediate alloy. The mass percentage of La to Ce in the Al-20(LaCe) alloy is 13:7.
[0038] S2: After all the intermediate alloy has completely melted, a third refining agent (hexachloroethane) is added to purify the melt and remove impurities. The melt is then cooled to 720℃ and cast into an ingot, which is then air-cooled. The tensile strength of the as-cast product is 169.6 MPa, the yield strength is 93.7 MPa, and the elongation is 4.77%. The tensile strength of the obtained as-cast product at 200℃ is 109.1 MPa, the yield strength is 83.9 MPa, and the elongation is 5.30%. S3: The material is taken from 1 cm below the ingot and subjected to an annealing process of 400℃ / 2h + 530℃ / 5h quenching, followed by a two-stage aging treatment of 100℃ / 2h + 160℃ / 10h to obtain a heat-resistant aluminum-silicon alloy material.
[0039] S4: The Brinell hardness of the ingot was measured to be 70.3HB, the Brinell hardness after annealing and aging treatment was 72.3HB, the Brinell hardness after heat exposure at 200℃ / 300h was 72.1HB, and the Brinell hardness after heat exposure at 300℃ / 300h was 66.1HB.
[0040] The room temperature mechanical properties of the annealed product are: tensile strength 175.5 MPa, yield strength 95.6 MPa, and elongation 4.37%.
[0041] The room temperature mechanical properties of the annealed product after heat exposure at 300℃ for 300h are as follows: tensile strength 81.2MPa, yield strength 65.1MPa, and elongation 6.61%.
[0042] Example 2
[0043] S1: According to the designed chemical formula: Al-2Si-2.5(LaCe)-1Ho-1Nd-0.5Yb-0.3Zr, 2325g Al, 500g Al-20Si, 625g Al-20(LaCe), 500g Al-10Ho, 500g Al-10Nd, 250g Al-10Yb, and 300g Al-5Zr are sequentially added to a pit-type resistance furnace at 800℃ for melting. During this process, slag is removed from the melt before each addition of the intermediate alloy. The mass percentage of La to Ce in the Al-20(LaCe) alloy is 13:7.
[0044] S2: After all the intermediate alloys have completely melted, a third refining agent (hexachloroethane) is added to purify the melt and remove impurities. The melt is then cooled to 720℃ and cast into an ingot, which is then air-cooled. The room temperature mechanical properties of the as-cast product are: tensile strength 132.7MPa, yield strength 59.2MPa, and elongation 5.91%.
[0045] S3: Material is taken from 1 cm below the ingot, annealed at 400℃ / 2h + quenched at 530℃ / 5h, followed by a two-stage aging treatment at 100℃ / 2h + 160℃ / 10h to obtain a heat-resistant aluminum-silicon alloy material. The room temperature mechanical properties of the annealed product are: tensile strength 137.5MPa, yield strength 65.2MPa, and elongation 5.62%.
[0046] Example 3
[0047] S1: According to the designed chemical formula: Al-3Si-3.5(LaCe)-2Ho-2.5Nd-1Yb-0.5Zr, 125g Al, 750g Al-20Si, 875g Al-20(LaCe), 1000g Al-10Ho, 1250g Al-10Nd, 500g Al-10Yb, and 500g Al-5Zr are sequentially added to a pit-type resistance furnace at 800℃ for melting. During this process, slag is removed from the melt before each addition of the intermediate alloy. The mass percentage of La to Ce in the Al-20(LaCe) alloy is 13:7.
[0048] S2: After all the intermediate alloys have completely melted, a third refining agent (hexachloroethane) is added to purify the melt and remove impurities. The melt is then cooled to 720℃ and cast into an ingot, which is then air-cooled. The room temperature mechanical properties of the as-cast product are: tensile strength 145.2 MPa, yield strength 76.4 MPa, and elongation 5.41%.
[0049] S3: Material is taken from 1 cm below the ingot, annealed at 400℃ / 2h + quenched at 530℃ / 5h, followed by a two-stage aging treatment at 100℃ / 2h + 160℃ / 10h to obtain a heat-resistant aluminum-silicon alloy material. The room temperature mechanical properties of the annealed product are: tensile strength 153.9MPa, yield strength 85.1MPa, and elongation 5.07%.
[0050] Example 4
[0051] S1: According to the designed chemical formula: Al-2.5Si-3 (LaCe)-1.5Ho-1.5Nd-1Yb-0.4Zr, 1350g of Al, 625g of Al-20Si, 625g of Al-20(LaCe), 750g of Al-10Ho, 750g of Al-10Nd, 500g of Al-10Yb, and 400g of Al-5Zr are sequentially added to a pit-type resistance furnace at 800℃ for melting. During this process, slag is removed from the melt before each addition of the intermediate alloy. The mass percentage of La to Ce in the Al-20(LaCe) alloy is 13:7.
[0052] S2: After all the intermediate alloys have completely melted, a third refining agent (hexachloroethane) is added to purify the melt and remove impurities. The melt is then cooled to 720℃ and cast into an ingot, which is then air-cooled. The room temperature mechanical properties of the as-cast product are: tensile strength 139.6 MPa, yield strength 65.8 MPa, and elongation 5.54%.
[0053] S3: Material is taken from 1 cm below the ingot, annealed at 400℃ / 2h + quenched at 530℃ / 5h, followed by a two-stage aging treatment at 100℃ / 2h + 160℃ / 10h to obtain a heat-resistant aluminum-silicon alloy material. The room temperature mechanical properties of the annealed product are: tensile strength 148.2MPa, yield strength 74.7MPa, and elongation 5.70%.
[0054] Comparative Example 1
[0055] All other conditions are the same as in Example 1, except that:
[0056] In S1: according to the designed chemical formula: Al-2.4Si-3 (LaCe)-2Ho-2Nd-0.4Zr, each raw material is prepared; the room temperature mechanical properties of the resulting annealed product are: tensile strength 132.5MPa, yield strength 61.8MPa, and elongation 2.16%.
[0057] Comparative Example 2
[0058] All other conditions are the same as in Example 1, except that:
[0059] In S1: according to the designed chemical formula: Al-2.4Si-3 (LaCe)-2Ho-0.7Yb-0.4Zr, each raw material is prepared; the room temperature mechanical properties of the resulting annealed product are: tensile strength 159.2MPa, yield strength 80.5MPa, and elongation 2.65%.
[0060] Comparative Example 3
[0061] All other conditions are the same as in Example 1, except that:
[0062] In S1: According to the designed chemical formula: Al-2.4Si--2Ho-2Nd-0.7Yb-0.4Zr, each raw material is prepared; the room temperature mechanical properties of the annealed product are: tensile strength 126.9MPa, yield strength 58.4MPa, and elongation 3.53%.
Claims
1. A heat-resistant aluminum-silicon alloy material, characterized in that: The chemical formula of the heat-resistant aluminum-silicon alloy material is: Alx1Six2(LaCe)x3Hox4Ndx5Ybx6Zr; the mass percentage content of the alloy constituent elements is: Si 2-3%, La+Ce 2.5-3.5%, Ho 1-2.5%, Nd 1-2.5%, Yb 0.5-1%, Zr 0.3-0.5%, and the remainder is Al, incidental elements and unavoidable impurities; The ingot is subjected to annealing and aging processes in sequence, followed by water cooling. The annealing process involves quenching at 400℃ for 2 hours and then at 530℃ for 5 hours, followed by aging at 160℃ for 12 hours.
2. The heat-resistant aluminum-silicon alloy material according to claim 1, characterized in that: The value of x1 is 2, the value of x2 is 2.5, the value of x3 is 1, the value of x4 is 1, the value of x5 is 0.5, and the value of x6 is 0.
3. or The value of x1 is 3, the value of x2 is 3.5, the value of x3 is 2, the value of x4 is 2.5, the value of x5 is 1, and the value of x6 is 0.
5.
3. The heat-resistant aluminum-silicon alloy material according to claim 1, characterized in that: The value of x1 is 2.5, the value of x2 is 3, the value of x3 is 1.5, the value of x4 is 1.5, the value of x5 is 1, and the value of x6 is 0.
4.
4. The heat-resistant aluminum-silicon alloy material according to claim 1, characterized in that: The value of x1 is 2.4, the value of x2 is 3, the value of x3 is 2, the value of x4 is 2, the value of x5 is 0.7, and the value of x6 is 0.
4.
5. The heat-resistant aluminum-silicon alloy material according to claim 1, characterized in that: The mass percentages of La and Ce are 13:
7.
6. A method for preparing the heat-resistant aluminum-silicon alloy material as described in any one of claims 1-5, characterized in that, Includes the following steps: Step 1: Raw material mixing: According to the stated mass percentage, alloys of different compositions are mixed and added to the smelting furnace for smelting; Step 2: Ingot preparation: After refining with refining agent at least twice, the ingot is cast and air-cooled; In Step 2, after refining at least twice, the temperature of the melt is reduced to 720°C and then poured into a mold preheated to 200°C and coated with zinc oxide coating. Step 3: Heat treatment process: The ingot raw material is heat treated to obtain heat-resistant aluminum-silicon alloy material; In step 3, the ingot annealing process involves quenching at 400℃ / 2h + 530℃ / 5h, followed by a two-stage aging treatment at 100℃ / 2h + 160℃ / 10h to obtain a heat-resistant aluminum-silicon alloy material. In step 1, the smelting temperature is 800-820℃.
7. The method for preparing a heat-resistant aluminum-silicon alloy material according to claim 6, characterized in that: In step 1, the heating rate of the smelting furnace is 4-6℃ / min.
8. The method for preparing a heat-resistant aluminum-silicon alloy material according to claim 6, characterized in that: The refining agents used in refining include hexachloroethane.
9. The method for preparing a heat-resistant aluminum-silicon alloy material according to claim 6, characterized in that: After being exposed to continuous heat at 200℃ for 300 hours, the Brinell hardness of the resulting two-stage aging product decreased by less than or equal to 0.1% compared to the product after two-stage aging.
10. The method for preparing a heat-resistant aluminum-silicon alloy material according to claim 6, characterized in that: After the obtained two-stage aging product is continuously exposed to heat at 300℃ for 300 hours, its Brinell hardness decreases by less than or equal to 10%, or even less than or equal to 9%, compared to the product after two-stage aging.
Citation Information
Patent Citations
High-performance cast aluminum-silicon alloy and preparation method thereof
CN116005022A
Heat-resistant aluminum-silicon alloy material and preparation method thereof
CN118773491A